Evaluation Of healthy nutrition index-2015, dental health and oral flora relationship in school-age children - KARĞIN, DİCLE; OMURTAG KORKMAZ, BURCU İREM (My University, 2021)
Objective: The aim of the study is to evaluate the role of diet quality and oral flora on the dental health in the childhood period. Methods: A cross-sectional study was carried out with the participation of 98 children aged 9-14 and their parents who applied to the Pedodontics Clinic Dental Faculty of Marmara University. The decayed, missing, filled tooth and surfaces and DMFT, DMFS indexes were determined through visual dental examination. Anthropometric measurements and saliva samples, as well as 24 h food consumption records, were taken from each child. Saliva samples were analysed microbiologically. To evaluate dietary quality from intakes Healthy Eating Index-2015 (HEI-2015) scores were calculated. Results: The mean age of children was 10.8±1.5 and study sample compromised 44.9% males and 55.1% females. 75% of the children had normal height and 58.2% of them had normal BMI according to World Health Organisation (WHO) references. The mean number of decayed tooth and surface was 3.07±2.35; 4.34±3.78 respectively and the mean number of DMFT and DMFS indexes were 5.88±2.31; 8.05±4.58 respectively. The mean number of decayed, missing, filled teeth and DMFT, DMFS scores were found to be higher in children with poor diets (according to HEI-2015) but the difference was not statistically significant (p>0.05). The presence of lactobacilli in saliva samples of 5.5% of the children was observed and children have lactobacilli in their saliva samples had more decayed teeth (p<0.05). Conclusion: The study findings illustrate the relationship between decay development and lactobacilli. Further studies with high sample sizes are needed to examine the diet quality and oral health.
Keywords: TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Healthy eating index; Dental caries; Diet quality; Childhood; Oral flora; EATING INDEX; GLOBAL BURDEN; DIET QUALITY; CARIES; BACTERIA; PREDICTOR; DISEASES; UPDATE; : Healthy eating index; Dental caries; Diet quality; Childhood; Oral flora